'Stylo-mandibular complex' fracture from a maxillofacial surgeon's perspective – review of the literature and proposal of a management algorithm. Issue 3 (March 2016) - Gayathri, G.; Elavenil, P.; Sasikala, B.; Pathumai, M.; Krishnakumar Raja, V.B.
Abstract: The incidence of fractures of styloid process, either in isolation or association with mandibular fractures, is rare, and frequently overlooked. When present, they pose clinical dilemma in diagnosis and management. Proper management of styloid fractures is essential, not just to alleviate the patients' symptoms, but also to prevent potential complications like post-traumatic styloid syndrome and injury to adjacent vital structures. This article features a review of literature on 'styloid fracture concomitant with mandibular fracture' along with a case report. The article explores the biomechanics resulting in styloid fracture especially when co-existing with mandibular fractures. The article also enumerates the clinical features of this unusual clinical phenomenon and aims at rationalizing the need for its medical or surgical management. A simple protocol for the management of 'stylo-mandibular complex' fracture has been proposed.